Natural compounds targeting major cell signaling pathways: a novel paradigm for osteosarcoma therapy. Issue 1 (December 2017) - Angulo, Pablo; Kaushik, Gaurav; Subramaniam, Dharmalingam; Dandawate, Prasad; Neville, Kathleen; Chastain, Katherine; Anant, Shrikant
Abstract Osteosarcoma is the most common primary bone cancer affecting children and adolescents worldwide. Despite an incidence of three cases per million annually, it accounts for an inordinate amount of morbidity and mortality. While the use of chemotherapy (cisplatin, doxorubicin, and methotrexate) in the last century initially resulted in marginal improvement in survival over surgery alone, survival has not improved further in the past four decades. Patients with metastatic osteosarcoma have an especially poor prognosis, with only 30% overall survival. Hence, there is a substantial need for new therapies. The inability to control the metastatic progression of this localized cancer stems from a lack of complete knowledge of the biology of osteosarcoma. Consequently, there has been an aggressive undertaking of scientific investigation of various signaling pathways that could be instrumental in understanding the pathogenesis of osteosarcoma. Here, we review these cancer signaling pathways, including Notch, Wnt, Hedgehog, phosphatidylinositol-4, 5-bisphosphate 3-kinase (PI3K)/AKT, and JAK/STAT, and their specific role in osteosarcoma. In addition, we highlight numerous natural compounds that have been documented to target these pathways effectively, including curcumin, diallyl trisulfide, resveratrol, apigenin, cyclopamine, and sulforaphane. We elucidate through references that these natural compounds can induce cancer signaling pathway manipulation and possibly facilitate new treatment modalities for osteosarcoma.